Analisis Hukum terhadap Pengaruh Tidak Adanya Employee Branding bagi Pekerja Berdasarkan Peraturan Menteri Ketenagakerjaan Nomor 6 Tahun 2016 - S, Safiyah; Ambarwati, Mega Dwi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In the era of competitive industry and organizational identity, companies have increasingly required employees to contribute not only through their tasks but also by supporting the company’s public image, a practice known as employee branding. However, in Indonesia, there is currently no specific legal regulation that governs the legal obligation of workers to perform employee branding, creating legal ambiguity and potential conflict between workers and employers. This paper aims to analyze the legal consequences for employees who do not fulfill employee branding duties and to examine the regulatory gap in Indonesian labor law regarding this issue. The research adopts a qualitative normative method using library research by reviewing statutory regulations, legal principles, and related literature. The findings show that the absence of explicit legal norms in Law Number 13 of 2003 concerning Manpower and other labor-related regulations causes companies to rely on internal policies, which may not always align with workers’ fundamental rights such as privacy and freedom of expression. Legal consequences for non-compliance vary depending on contractual clauses, ranging from verbal warnings to termination of employment, though such sanctions must be legally grounded to avoid unlawful labor practices. This study recommends that employee branding be regulated under clear legal instruments such as Ministerial Regulations, contractual clauses, and collective labor agreements (PKB), while ensuring the participation of labor unions and ethical considerations. A balance between company interests and workers’ rights is crucial to prevent legal disputes and to implement employee branding as a fair and constructive organizational strategy.